Die rol van ’n mentor vir seuns tydens die oorgangsfase van die laat-middelkinderjare na adolessensie - Steytler, J. P. D. (Koers, 2008)
The role of a mentor for boys during their transition phase from late middle childhood to adolescence Boys in their late middle childhood experience far-reaching changes in their lives. Reaching puberty and experiencing the transition from childhood to adolescence causes immense stress and tension. The intensity of the relationship between father and son decreases many times, while involvement with the peer group increases. This article focuses on the experiences of the boys in their late middle childhood regarding their biological father and the influence of the family hierarchy. As alternative father figure, the focus falls on a mentor. The longing for a mentor and the expectations of the boys in their late middle childhood in this regard are explored in this article.